Organic Amendments Improve the Quality of Coal Gob Spoils: A Sustainable Mining Waste Reclamation Method - Zhiming Zhang; Anshuman Satpathy; Kirby Morris; Abhishek RoyChowdhury; Rupali Datta; Dibyendu Sarkar (Applied Sciences)
Coal mine tailings can lead to a range of environmental problems, including toxic metal contamination, soil erosion, acid mine drainage, and increased salinity. Mine spoils from coal mining activities accumulated as gob piles are difficult to reclaim due to constraints such as a steep slope, unsuitable pH, insufficient nutrient supply, metal toxicity, low water-holding capacity, and poor soil structure. We investigated the efficiency of low-cost amendments on coal gob spoils from Carthage Coal Field (CCF) in New Mexico in improving the quality of coal gob spoils. Gob spoil was incubated for 90 days with various rates of organic amendments such as biochar, compost, and a biochar–compost mix. Gob spoil quality parameters such as the pH, water-holding capacity, and total and plant-available nitrogen and phosphorus content of the gob spoil were measured over a period of 90 days. Both biochar and compost amendment led to a significant increase (40–60% for biochar and 70% for compost, p < 0.05) in water-holding capacity of the coal gob spoil. Plant-available nitrogen content increased from <200 mg N/kg to between 400 and 800 mg N/kg in the amended gob spoil. The period of incubation was a significant factor in the improvement of plant-available nitrogen content. Plant-available phosphorus content also increased; compost amendment was more effective than biochar in increasing plant-available P. This study provides crucial information about the optimum organic amendments that would help in optimizing a sustainable reclamation method for CCF.